A Study of the Relationship between System Testability and Modularity. Issue 1 (13th September 2016) - Efatmaneshnik, Mahmoud; Ryan, Michael
Abstract: Modularity is one approach to design that, amongst other design attributes, facilitates testability. However, the relationship between the type of modularization and system testability is under‐researched. In this paper we present a probabilistic model of testability that enables us to study the relationship between modularity and testability. In particular, we focus on the costs and benefits associated with the particular modularizations selected for the sole purpose of system testability. We show that adopting and appropriate testing architecture through careful modularization can greatly enhance efficiency and effectiveness of system testing.